Development of membrane lipids in the surfactin producer Bacillus subtilis - Seydlová, G; Svobodová, J (Folia microbiologica, 2008)
Processes occurring in the cytoplasmic membrane of the surfactin producer Bacillus subtilis were examined during a 3-d cultivation. The fatty acid composition was found to be almost stable within this interval, except for the early stationary phase when the nonbranched, mostly C(16:0) and C(18:0) (high melting fatty acids), prevailed transiently in the membrane. As for phospholipids, phosphatidylglycerol and phosphatidylethanolamine, representing 73 % of the total in the membranes of exponential cells were partly replaced by cardiolipin, which gradually rose from 5 to 28 % at the end of cultivation. In parallel, steady-state fluorescence anisotropy (r (s)) measurements with 1,6-diphenyl-1,3,5-hexatriene (DPH) indicated a remarkable increase of r (s) DPH during the long-term cultivation and implied a continuous rigidization of the membrane interior. By contrast, the almost constant values of r (s) 1-(4-trimethylammoniumphenyl)-6-phenyl-1,3,5-hexatriene 4-toluenesulfonate (TMA-DPH) reflected stable microviscosity of the membrane surface region. Thus, the significant increase of high melting fatty acids and cardiolipin in the cytoplasmic membrane together with the progressive rigidization of the membrane interior reflected the cell adaptation to adverse conditions.
Keywords: Fluorescence Polarization; Bacillus subtilis; Membrane Lipids; fluorescenční polarizace; Kinetics; Cell Membrane; Peptides, Cyclic; lipopeptidy; Lipopeptides; buněčná membrána; kinetika; cyklické peptidy; membránové lipidy